Emotional body-word conflict evokes enhanced n450 and slow potential. - Jianling Ma (Public Library of Science (PLoS), 2014)
Emotional conflict refers to the influence of task irrelevant affective stimuli on current task set. Previously used emotional face-word tasks have produced certain electrophysiological phenomena, such as an enhanced N450 and slow potential; however, it remains unknown whether these effects emerge in other tasks. The present study used an emotional body-word conflict task to investigate the neural dynamics of emotional conflict as reflected by response time, accuracy, and event-related potentials, which were recorded with the aim of replicating the previously observed N450 and slow potential effect. Results indicated increased response time and decreased accuracy in the incongruent condition relative to the congruent condition, indicating a robust interference effect. Furthermore, the incongruent condition evoked pronounced N450 amplitudes and a more positive slow potential, which might be associated with conflict-monitoring and conflict resolution. The present findings extend our understanding of emotional conflict to the body-word domain.